--Wyrażenia algebraiczne--

Doprowadz do najprostszej postaci:

a) -3(x³+4x-2)+2x(x²-3x)
b) (3-4x²+5x)-(-3x+5x²+3)
c) (4a²-3ab-0,1a)+(-14a+2ab+0,1a)
d) -(x²-2xy)-(xy-2x²+4)+3xy-x²
e) 2ab²-(4a²b-3b²a)-[-(-12ba²+3a²b²)]+16a²b
f) (x²-6x+18):3+(x²-3x+5):2

Bardzo prosze o pomoc :-)

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T17:57:15+02:00
A) -3(x³+4x-2)+2x(x²-3x)=-3x³-12x+6+2x³-6x²==x³-4x²-12x+6
b) (3-4x²+5x)-(-3x+5x²+3)=3-4x²+5x+3x-5x²-3=-9x²+8x
c) (4a²-3ab-0,1a)+(-14a+2ab+0,1a)=4a²-3ab-0,1a-14a+2ab+0,1a=
4a²-ab-14a
d) -(x²-2xy)-(xy-2x²+4)+3xy-x²=-x²+2xy-xy+2x²-4+3xy-x²=
4xy-4
e) 2ab²-(4a²b-3b²a)-[-(-12ba²+3a²b²)]+16a²b=
2ab²-4a²b+3b²a-(+12ba²-3a²b²)+16a²b=
2ab²-4a²b+3b²a-12ba²+3a²b²+16a²b=5ab²-12a²b+3a²b²
f) (x²-6x+18):3+(x²-3x+5):2=⅓x²-2x+6+½x²-³/₂x+⁵/₂=
⁵/₆x²-3,5x8,5
2010-04-13T17:59:17+02:00
A) -3(x³+4x-2)+2x(x²-3x)=-3x³-12x+6+2x³-6x²=-x³-6x²-12x+6
b) (3-4x²+5x)-(-3x+5x²+3)=3-4x²+5x+3x-5x²-3=-9x²+8x
c) (4a²-3ab-0,1a)+(-14a+2ab+0,1a)=4a²-3ab-0,1a-14a+2ab+0,1a=4a²-ab-14a
d) -(x²-2xy)-(xy-2x²+4)+3xy-x²=-x²+2xy-xy+2x²-4+3xy-x²=4xy-4
e) 2ab²-(4a²b-3b²a)-[-(-12ba²+3a²b²)]+16a²b=
=2ab²-4a²b-3b²a-[12ba²-3a²b²]+16a²b=-ab²+12a²b-12ba²+3a²b²=
=-ab²+3a²b²
f) (x²-6x+18):3+(x²-3x+5):2=1/3x²-2x+6+1/2x²-3/2x+5/2=
=2/6x²+3/6x²-3,5x+9,5=5/6x²-3,5x+9,5
1 1 1